Évolution des évènements pluviométriques et de crues extrêmes dans la commune urbaine de Mopti, Mali - Abdoulkadri Oumarou Touré; Hamidou Diawara; Fatoumata Maïga; Issa Ouattara; Bouramadiè Coulibaly (VertigO, 2025)
Flood-prone areas in the urban commune of Mopti have begun to be occupied by settlements since the droughts of the 1970s and 1980s. The increase in extreme rainfall and flooding, combined with inappropriate land use, has increased the risk of flooding. The objective of this study is to analyse the factors of floods in this new climatic context characterised by extreme events. The data of rainfall and daily maximum coasts from 1960-2013 and 1944-2022 respectively, at the meteorological and hydrological stations of Mopti were analyzed. Pettitt and Mann-Kendall tests on these variables have made it possible to identify sub-periods and to analyse trends. Then, an intercomparison of the empirical distributions and the Gumbel and Pearson type-3 laws made it possible to use the latter for the estimation of the quantiles of different frequencies of the variables studied. Thus, three sub-periods have been identified for maximum coasts (1944-1971, 1972-1993, 1994-2022) with a significant downward trend between 1972-1993, unlike the other two where the trends are not significant. Through frequency analysis, it is established that 1944-1971 was the most critical period for floods of any threshold. The daily duration of the biennial flood has an upward trend, from 70.4 for 1944-1971, to 4.3 for 1972-1993, and to 10.1 for 1994-2022. Finally, floods of rarer frequencies (return times of 10 and 20 years) have not occurred in Mopti since 1971.